A Comparative Study Of The Function Of Small Talk Between Arab And Malay Communication - Mohamad, Norhayuza; Mamat, Anis Nabilah; Zakaria, Muhamad Zaidi; Puasa, Bashasunnahar; Mohd Ramli, Zuraini (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Small talk is defined as an informal dialogue or conversation that does not cover an important topic of conversation. It is a polite conversation about insignificant matters. To date, the small talk function of Arab and Malay communication has not been clearly understood due to a lack of research in this field. This study compares the part of small talk in Arab and Malay communication based on three communication phases: beginning, middle, and closing. The study is descriptive and employs a qualitative approach. The data from the small talk was analyzed using Malinowski's Phatic Communion Theory (1923). The researchers obtained data from an Arabic drama called